Anatomical, palynological and karyological remarks of Silene brevicalyx and Silene ozyurtii (Caryophyllaceae) - Atasagun, Bayram; Aksoy, Ahmet; Marti̇n Esra (Phytotaxa, 2016)
Anatomical, palynological, karyological and morphological seed characters of Silene brevicalyx and S. ozyurtii (Caryophyllaceae) were investigated for the first time. S. brevicalyx grows on serpentine rocky slopes and open forest in Muğla province (southwestern Turkey), while S. ozyurtii is an East Mediterranean element growing on serpentine stony slopes and again open forest. Anatomically, cross-section of root of both species have a periderm as the protective tissue at the outermost layer and locally druse crystals are encountered in cortex layer. Stems have a thick well-developed sclerenchyma layer. The walls of outward sclerenchyma cells are wider than the walls of inward cells. Leaves are equifacial. Pollen are prolate-spheroidal, symmetry radially, polarity apolar, with aperture periporate, ornamentation microechinate-perforate. Seeds of both species are reniform, with surface concave and granulation coarse-medium, hylar zone recessed, dark-brown or fuscous coloured. Somatic chromosome numbers of 2n = 24 were found for both taxa. The karyotypes are analyzed for the first time for S. brevicalyx and S. ozyurtii. Ideograms of these taxa were drawn by use of an Image Analysis System.